Pengaruh Biaya Tenaga Kerja dan Biaya Pakan terhadap Pendapatan Usaha Peternakan Ayam Broiler di Kabupaten Sikka - Rikarda Bara; Wilhelmina Mitan; Yoseph Darius Purnama Rangga (Jurnal Mutiara Ilmu Akuntansi, 2025)
This study aims to examine and analyze the effect of labor costs and feed costs on the income of broiler chicken farming businesses in Sikka Regency. The background of this research is based on the fact that labor costs and feed costs are the largest expense components in broiler chicken farming, thus it is necessary to investigate their contribution to farmers’ income. This research applies a quantitative approach with a causal design to identify cause-and-effect relationships between variables. The population of the study consisted of 78 broiler chicken farming businesses in Sikka Regency, with the purposive sampling technique applied to determine the sample. Data were collected through documentation techniques within the observation period of 2022–2024. Data analysis was conducted using multiple linear regression with the aid of the Statistical Package for the Social Sciences (SPSS) software. The results show that partially, labor costs have a significant effect on business income, indicating that the more efficient the management of labor, the higher the income generated. Feed costs also have a significant effect on business income, as feed is the main factor determining the growth quality of broiler chickens. Simultaneously, labor costs and feed costs significantly influence the income of broiler chicken farming businesses in Sikka Regency. These findings emphasize the importance of cost efficiency in the management of broiler chicken farming businesses to increase income and strengthen the competitiveness of local farmers amid the increasingly competitive poultry industry.